Effect of timing of heat stress during grain filling in two wheat varieties under moderate and very high temperature - Song, W. F.; Zhao, L. J.; Zhang, X. M.; Zhang, Y. M.; Li, J. L.; Zhang, L. L.; Song, Q. J.; Zhao, H. B.; Zhang, Y. B.; Zhang, C. L.; Xin, W. L.; Sun, L. F.; et al. (The Indian Journal of Genetics and Plant Breeding, 2016)
In order to examine the effect of short periods heat stress on grain growth, two cultivars (Longmai26 and Longmai30) were grown in pots at two different diurnal temperatures (32/22°C; 25/15°C) in climate-controlled growth cabinets and exposed to a 5-day heat stress (38/22°C) at 5-day intervals throughout grain filling after anthesis.The results indicated that long periods of moderate high temperature (>30°C) have higher effect than short periods of heat stress (5 days with maximum 38°C for 6h each day). However, plants grown at the moderate temperature (25/15°C) showed a greater response to a short period of heat stress than plants grown at the high temperature (32/22°C). At elevated temperatures, the change in the rate of grain filling is smaller than duration of grain filling.The high grain-filling rate and high potential grain weight should be used as a criterion in selecting for high temperature tolerance in wheat.